Origin of Syrinx Fluid in Syringomyelia: A Physiological Study. Issue 2 (30th March 2018) - Heiss, John D; Jarvis, Katie; Smith, René K; Eskioglu, Eric; Gierthmuehlen, Mortimer; Patronas, Nicholas J; Butman, John A; Argersinger, Davis P; Lonser, Russell R; Oldfield, Edward H
Abstract: BACKGROUND: The origin of syrinx fluid is controversial. OBJECTIVE: To elucidate the mechanisms of syringomyelia associated with cerebrospinal fluid pathway obstruction and with intramedullary tumors, contrast transport from the spinal subarachnoid space (SAS) to syrinx was evaluated in syringomyelia patients. METHODS: We prospectively studied patients with syringomyelia: 22 with Chiari I malformation and 16 with SAS obstruction-related syringomyelia before and 1 wk after surgery, and 9 with tumor-related syringomyelia before surgery only. Computed tomography-myelography quantified dye transport into the syrinx before and 0.5, 2, 4, 6, 8, 10, and 22 h after contrast injection by measuring contrast density in Hounsfield units (HU). RESULTS: Before surgery, more contrast passed into the syrinx in Chiari I malformation-related syringomyelia and spinal obstruction-related syringomyelia than in tumor-related syringomyelia, as measured by (1) maximum syrinx HU, (2) area under the syrinx concentration-time curve (HU AUC), (3) ratio of syrinx HU to subarachnoid cerebrospinal fluid (CSF; SAS) HU, and (4) AUC syrinx/AUC SAS. More contrast (AUC) accumulated in the syrinx and subarachnoid space before than after surgery. CONCLUSION: Transparenchymal bulk flow of CSF from the subarachnoid space to syrinx occurs in Chiari I malformation-related syringomyelia and spinal obstruction-related syringomyelia. Before surgery, more subarachnoid contrast entered syringes associated with CSF pathway obstruction than with tumor, consistent with syrinx fluid originating from the subarachnoid space in Chiari I malformation and spinal obstruction-related syringomyelia and not from the subarachnoid space in tumor-related syringomyelia. Decompressive surgery opened subarachnoid CSF pathways and reduced contrast entry into syringes associated with CSF pathway obstruction.